Nigerian Bankers Question & Answers : Accounting II - Johnson, I.E. (Lagos, Nigeria : Akhimieho & Co, 1987)
This book contain Questions and Answers on Accounting suitable for students of accountancy in polytechnics and University as well as those preparing for professional examinations in accounting.
Includes illustrations
jbi, 22/03/2018, rpm 01/02/2019
Loans
Keywords: Accounting; Nigeria